Value of Resistin in Early Onset Neonatal Sepsis - Ozdemir, Abdurrahman Avar; Elgormus, Yusuf (Journal of Child Science, 2017)
The diagnosis of neonatal sepsis is usually difficult because the sign and symptoms are nonspecific. Although C-reactive protein (CRP) and procalcitonin (PCT) are the most commonly used auxiliary tests, they are not reliable enough markers to be used for diagnosis of neonatal sepsis. This study aimed to evaluate the efficacy of resistin in diagnosing early onset neonatal sepsis and to compare its effectiveness to CRP and PCT. This prospective study was performed in the neonatal intensive care unit of Medicine Hospital between June and September 2016. Twenty-nine infants in the sepsis group and 33 infants in the control group were recruited. The Töllner scoring system was used for clinical signs. The hematologic parameters were evaluated using the Manroe and Rodwell scoring systems. The blood samples for CRP, PCT, and resistin were collected at admission (T0), and at 72 hours (T3). Mean plasma resistin level at T0 was 54.20 ± 39.3 ng/mL in the sepsis group and 34.92 ± 6.9 ng/mL in the control group. The sensitivity at T0 for resistin was 76%, and the specificity was 67%. The values of area under the curve (AUC) for CRP, PCT, and resistin were 0.84, 0.66, and 0.72, respectively. We found the diagnostic value of resistin to be lower than CRP, although its plasma levels were elevated. Therefore, we propose that resistin has limited value in diagnosis and follow-up of early-onset neonatal sepsis.
Keywords: newborn; neonatal sepsis; resistin